Making women’s travel literature in Andalusia visible: Annie J. Harvey’s Cositas Españolas, or Everyday Life in Spain (1875) - Rivas-Carmona, María Del Mar; Jiménez-Miranda, Marta (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper is dedicated to the work of British1 female travellers who visited Spain and, more specifically, Andalusia, from the 18th century to the present. Their works offer a sensitive, first-hand view that is different from that of their male contemporaries and, on numerous occasions, question or contradict the supposed myths, comments, and opinions of their compatriots, even those of renowned Hispanophiles as Richard Ford or George Borrow. Unfortunately, practically all the works on Spain by female travellers have remained forgotten, ignored, or silenced, and have not been translated into other languages. With the aim of making women’s contributions to travel literature more visible, this paper offers an unpublished chronological list of women travellers in Andalusia and their works from the 18th century to the present, compiled thanks to consultations with the collections of the library of the Instituto Cervantes in London. As a sample of the sensitive and emotional vision that appreciates the essence of the rural and human landscape of Andalusia, compared to other technical accounts of male writers, we analyse Cositas Españolas, or Every Day Life in Spain (1875) by Annie Jane Harvey, a work not yet translated into Spanish and whose visibility we claim from this work. The study shows Harvey to be a privileged “observer”, whose alternative vision to that of other male travellers proves an optimistic defence of the values of the Spanish people.